Experimental evidence for bipolaron condensation as a mechanism for the metal-insulator transition in rare-earth nickelates - Jacob Shamblin (Nature Portfolio, 2018)
Rare-earth nickelates undergo a metal-to-insulator transition accompanied by the formation of ordered lattice distortions, but the role of the lattice in the metallic phase remains unclear. Here the authors provide evidence that the metal is a polaronic liquid that freezes into the insulating state.